The role of caspases as executioners of apoptosis. (28th February 2022) - Kumar, Sharad; Dorstyn, Loretta; Lim, Yoon
Abstract : Caspases are a family of cysteine aspartyl proteases mostly involved in the execution of apoptotic cell death and in regulating inflammation. This article focuses primarily on the evolutionarily conserved function of caspases in apoptosis. We summarise which caspases are involved in apoptosis, how they are activated and regulated, and what substrates they target for cleavage to orchestrate programmed cell death by apoptosis.